ANALYSIS OF TRAFFIC ACCIDENTS ON RAYA PELTONG ROAD – ARTODUNG PAMEKASAN DISTRICT - Wasiluddin; Ahmad Fatoni; Fairus Zabadi (Journal Innovation of Civil Engineering (JICE), 2023)
The Peltong-Artodung Highway, Pamekasan Regency has a high accident rate, a length of ± 2 km, and an effective road width of ± 6 m which is an area that has enough potential for the movement of traffic flow because it is a connecting road between Pamekasan City and Sumenep City, along the way there are also offices, schools, markets, shops, and residential areas. This analysis was conducted to determine the causal factors that influence the occurrence of traffic accidents. The data needed in this analysis consists of primary data and secondary data. Primary data consists of street names, number of lanes, lane widths, and LHR obtained from direct survey results in the field. The secondary data needed is a map of the research location, and data on traffic accidents. The data obtained is then analyzed by classifying accidents based on the factors that cause traffic accidents. The main factor in traffic accidents on Jalan Raya Pelting-Artodung (Jl. Lintas Pamekasan-Sumenep) is human beings, the age of the most traffic accident victims is 16-30 years old, the largest number of accidents occur at 06.00 to 20.00 as many as 63 .44% which is rush hour and the work of the accident perpetrators is dominated by men. Efforts that can be made to reduce the number of accidents on Jalan Raya Peltong-Artodung (Jl. Lintas Pamekasan-Sumenep), namely: providing traffic education and strict sanctions for road users who violate traffic rules and the installation of signs must be by Decree of the Minister of Transportation No. 61 of 1993 concerning Traffic Signs. Keywords: Peltong-Artodung Highway; Accident Characteristics; Victims.